PENGARUH UKURAN PERUSAHAAN, SOLVABILITAS, PROFITABILITAS, UKURAN KAP, DAN OPINI AUDIT TERHADAP AUDIT DELAY: PADA PERUSAHAAN PROPERTI & REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2020-2022 - Yovita Verlinda Sari; Rita Andini (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The goal of this research is to predict audit delay in Property and Real Estate businesess sector which is listed on the Indonesia Stock Exchange from 2020 until 2022, which is influenced by company size, solvency, profitability, public accounting firm (KAP) size, audit opinion. 92 companies became popilations in this research. After sampling using purposive sampling, 68 companies became the sample. Logistic regression is the analysis technique used in this research. This research results is partially the profitability have impact on audit delay, while the company size, solvency, public accounting firm (KAP) size and audit opinion has no impact on audit delay.